Alimentation et les perturbateurs endocriniens - MOUHOUBI , Zineb; OUARET , Rouida; ROUABAH , Qods; SABKHA , Abir; CHEROUAL , Amine (Encadrant) (Université Sétif1 Ferhat Abbas. Faculté de Médecine. Déppartement de Pharmacie, 2025)
This final-year study is set against a backdrop of growing concerns about food safety and environmental health. Its main objective is to assess the level of awareness among the Algerian population regarding endocrine disruptors (EDS) found in food, while also raising awareness of the health risks associated with these ubiquitous chemical substances. The first part of this work explores the fundamental concepts of healthy eating. A historical retrospective is provided to better understand the evolution of human dietary habits, from prehistory to the industrial era. Emphasis is placed on the characteristics of a balanced diet, its benefits for physical, mental, and emotional health, and its preventive role against noncommunicable diseases such as cardiovascular diseases, cancers, and metabolic and neurological disorders. The second part is devoted to the study of endocrine disruptors. These substances, whether natural or synthetic, can interfere with the human hormonal system even at very low doses. An in-depth analysis of several EDs notably bisphenol A, phthalates, parabens, pesticides, phytoestrogens, and heavy metalshighlights their mechanisms of action, sources, and potential effects on fertility, embryonic development, metabolism, the nervous system, and carcinogenesis. The third part addresses the main dietary exposure routes to EDs: canned foods, plastic packaging, processed products, and fruits and vegetables treated with pesticides. Prevention strategies are proposed, including regulation, health education, professional training for healthcare workers, and practical advice to reduce exposure. In the practical section, a survey was conducted on a sample of the Algerian population. It aimed to assess the level of knowledge about EDs, identify healthcare professionals’ (pharmacists, gynecologists, pediatricians) perceptions, and determine risky consumption habits. The results reveal a limited but growing awareness of the issue, especially among practitioners involved in maternal and child health. In conclusion, this thesis highlights the urgency of an integrated approach that combines nutrition, prevention, and health education. It calls for collective responsibility, both at the institutional and individual levels, to reduce daily exposure to EDs and ensure a healthier and safer food environment.
تندرج هذه الدراسة النهائية ضمن سياق تزايد الاهتمام بقضايا الأمن الغذائي والصحة البيئية. وتهدف بشكل رئيسي إلى تقييم لة للغدد الصماء الموجودة في الأغذية، مع العمل على توعية المجتمع )مستوى معرفة السكان الجزائريين بالمواد ال ُمع ِّط ) بالمخاطر الصحية المرتبطة بهذه المواد الكيميائية المنتشرة على نطاق واسع. تتناول الجزء الأول من هذا العمل المفاهيم الأساسية للتغذية الصحية، مع تقديم لمحة تاريخية لفهم تطور العادات الغذائية لدى الإنسان منذ عصور ما قبل التاريخ وحتى العصر الصناعي. يتم التركيز على خصائص النظام الغذائي المتوازن، وفوائده على الصحة الجسدية والعقلية والعاطفية، ودوره الوقائي ضد الأمراض غير المعدية مثل أمراض القلب والأوعية الدموية، والسرطانات، والاضطرابات الأيضية والعصبية. أما الجزء الثاني فيُخصص لدراسة المواد ال ُمع ِّطلة للغدد الصماء، وهي مواد ذات أصل طبيعي أو صناعي، قادرة على التأثيرفي النظام الهرموني للإنسان حتى بتركيزات ضئيلة جدا. تم تحليل عدد من هذه المواد بشكل معمق، مثل بيسفينول أ، الفثالات، البارابين، المبيدات، الفيتواستروجينات، والمعادن الثقيلة، مع توضيح آليات تأثيرها، ومصادرها، وآثارها المحتملة على الخصوبة، وتطور الجنين، والتمثيل الغذائي، والجهاز العصبي، والسرطنة. يتناول الجزء الثالث طرق التعرض الغذائي الرئيسية لهذه المواد، مثل الأغذية المعلبة، والتغليفات البلاستيكية، والمنتجات المصنعة، والفواكه والخضروات المعالجة بالمبيدات. كما تم اقتراح استراتيجيات وقائية تشمل التشريعات، والتثقيف الصحي، وتكوين المهنيين في القطاع الصحي، إلى جانب نصائح عملية للحد من التعرض لهذه المواد. في الجانب التطبيقي، أُجري استبيان على عينة من السكان في الجزائر، بهدف قياس مستوى المعرفة بخصوص المواد ال ُمع ِّطلة للغدد الصماء، وتحديد تصورات المهنيين الصحيين (من صيادلة، وأطباء نساء، وأطباء أطفال)، وكشف العادات الغذائية التي قد تشكل خطرا. وقد أظهرت النتائج وجود وعي محدود لكنه في تزايد، خصوصا لدى الممارسين الذين يتعاملون مع قضايا صحة الأم والطفل. ختاما، يبرز هذا البحث الحاجة الملحة إلى اعتماد مقاربة شاملة تجمع بين التغذية، والوقاية، والتثقيف الصحي. ويدعو إلى تحمل المسؤولية الجماعية، على المستويين المؤسساتي والمجتمعي، للحد من التعرض اليومي لهذه المواد وضمان بيئة صحة غذائية أكثر أمانا و